PROFIL VERTIKAL DAN LUAS BIDANG DINAMIKA HARIAN GRADIEN SUHU UDARA DI ATAS PERMUKAAN AIR LAUT DAN DI DALAM AIR LAUT - Erixio Mewoh; Patricia Silangen; Alfrie Rampengan; Christophil Medellu (Jurnal FisTa : Fisika dan Terapannya, 2021)
The temperature in sea water varies at each depth. The temperature of sea water at the surface is higher and the temperature at a deeper point is decreasing slowly. This study aims to determine the model of the temporal, spatial function, and dynamic models of daily temperature gradients above sea level and in sea water. This type of research is included in the type of exploratory research that is quantitative in nature. The research is in Tulaun hamlet, Lalumpe Village, Kombi District, Minahasa Regency, North Sulawesi Province, Indonesia. The research was conducted for 24 hours at 9 points, ranging from 0 cm, 10 cm, 30 cm, 60 cm, 100 cm, 150 cm, 220 cm, 300cm, to 400cm. The research variables were temperature and light intensity. Data processing in this study is to enter existing data into the Matlab application. The results of the study of changes in the functional model above sea level and in seawater are influenced by the heat absorption process of air temperature.